2013
DOI: 10.1002/cphc.201200762
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Push–Pull Distyrylfurans, Thiophenes and Pyridines by Fast and Ultrafast Techniques

Abstract: Time-resolved transient absorption and fluorescence spectroscopy with nano- and femtosecond time resolution were used to investigate the deactivation pathways of the excited states of distyrylfuran, thiophene and pyridine derivatives in several organic solvents of different polarity in detail. The rate constant of the main decay processes (fluorescence, singlet-triplet intersystem crossing, isomerisation and internal conversion) are strongly affected by the nature [locally excited (LE) or charge transfer (CT)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 57 publications
1
23
1
Order By: Relevance
“…Our research has been recently devoted to the investigation of the solvent effect on the spectra, the photophysics and the excited‐state dynamics of push–pull molecules, both neutral1216 and positively charged. Relevant results have been obtained for the latter,17, 18 which have shown a peculiar negative solvatochromic behavior and an interesting competition between the occurrence of solvation and photoinduced ICT during their excited‐state deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Our research has been recently devoted to the investigation of the solvent effect on the spectra, the photophysics and the excited‐state dynamics of push–pull molecules, both neutral1216 and positively charged. Relevant results have been obtained for the latter,17, 18 which have shown a peculiar negative solvatochromic behavior and an interesting competition between the occurrence of solvation and photoinduced ICT during their excited‐state deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] It has been observed that the extent of the NLO response and the two photon absorption cross-sections are strongly dependent upon the molecular structure of the pushpull molecules and are particularly affected by the strengths of the electron donor/acceptor groups. [14][15][16][17][18] This effect was observed not only in widely studied neutral donor-acceptor systems, but also in cationic chromophores bearing a methyl pyridinium or a methyl quinolinium as an electron deficient moiety, [19][20][21][22][23][24] whose photobehaviour has been less investigated so far and, therefore, not yet deeply understood. [14][15][16][17][18] This effect was observed not only in widely studied neutral donor-acceptor systems, but also in cationic chromophores bearing a methyl pyridinium or a methyl quinolinium as an electron deficient moiety, [19][20][21][22][23][24] whose photobehaviour has been less investigated so far and, therefore, not yet deeply understood.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most successful approaches to achieve high coefficients in NLO properties rely on the use of dipolar‐type molecules with a donor−bridge−acceptor (D−π−A) motif and quadrupolar‐type molecules with a D−π−A−π−D structure . The optical properties of these class of compounds depend not only on the optimal choice of the electron donor/acceptor pair but also on the nature of the π‐conjugated spacer; moreover, heterocyclic fragments have been considered to be promising for organic chromophores both as D/A moieties and as elements for the π conjugation ,…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] The optical properties of these class of compounds depend not only on the optimal choice of the electron donor/acceptor pair but also on the nature of the p-conjugated spacer; [19][20][21][22] moreover, heterocyclic fragments have been considered to be promising for organic chromophores both as D/A moieties and as elements for the p conjugation. [23,24] However, the optimization of NLO organic materials remains an extremely challenging task to solve, as organic chromo-phores often require multistage syntheses and product purification after each stage. Additional limitations, in practical terms, comprise low yields, low solubility in common solvents or aggregation phenomena that can further complicate the process of separation and purification of the final product, leading to a significant loss of material and an increase in its cost.…”
Section: Introductionmentioning
confidence: 99%